Identification of domains in rubella virus genomic RNA and capsid protein necessary for specific interaction. - Liu, Z (1996)
In rubella virus-infected cells, genomic 40S and subgenomic 24S RNAs are present in the cytoplasm of infected cells. However, encapsidation by rubella virus capsid protein is specific for 40S genomic RNA. As a first step toward understanding the assembly of rubella virus nucleocapsid at the molecular level, the interaction between capsid protein and genomic RNA was studied by Northwestern (RNA-protein) blot analysis. RNA probes prepared by in vitro transcription were used to localize the RNA sequence that participates in binding to the capsid protein. We have identified a 29-nucleotide RNA sequence (nucleotides 347 to 375) that is essential for the binding. By using overlapping synthetic peptides of capsid protein, a peptide domain (residues 28 to 56) that displays specific RNA-binding activity of capsid protein has been located. This result suggests that the specific recognition of viral RNA during rubella virus assembly involves, at least in part, the nucleocapsid protein.